PAI Learning Strategies to Strengthen Religious Literacy of Elementary School Children: A Comprehensive Literature Study - Agus Alfaya Arif; Muhammad Yoggi Aqsal Darmawan; Adnan Syah Sitorus; Mizlan Mizlan; Nelly Setiawati (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to comprehensively examine various Islamic Education (PAI) learning strategies that play a role in strengthening the religious literacy of elementary school children. Religious literacy at this level is an important foundation for the spiritual, moral, and social character development of students, especially amid the dynamics of technological developments and the flow of digital information. Through a literature review method, this study analyzes books, scientific articles, education policy reports, and relevant previous research results. The results of the study show that strengthening religious literacy can be optimized through several key strategies, namely contextual learning that links Islamic values to children's real experiences, the use of visually appealing and pedagogically attractive digital media, the use of storytelling as a means of internalizing values, habituation and role modeling in religious practice, and the application of collaborative learning models that encourage meaningful interaction. These findings confirm that efforts to improve religious literacy require an integrative, adaptive learning design that is in line with the developmental characteristics of students. This study is expected to provide a theoretical contribution to the development of more effective and relevant PAI learning practices in response to the challenges of modern education.